MODERN CORPORATE MANAGEMENT SYSTEM SCIENTIFIC APPROACHES TO THEORETICAL BASIS - Khabibullaeva Shirinkhan Tahir qizi (American Journals, 2023)
This article analyzes the understanding of the management system at corporate enterprises, the views of economists on this issue, reflects the principles of development of corporate governance, ways of implementation, as well as scientifically based conclusions on this issue.
Keywords: Corporate enterprises, corporate governance, rule, standard, guideline, principle, risk, sustainable, culture, stakeholder, principle, efficiency.